A method of extracting and purifying polyhydroxyalkanoate bioplastic. - Hassan, Mohd Ali; Voon, Phooi Tee; Shirai, Yoshihito; Phang, Lai Yee (2008)

(untitled)
Polyhydroxyalkanoates (PHA) is an intracellular polymer that is biologically synthesized by microorganisms as carbon and energy reverse material. This biodegradable material has properties similar to petrochemical thermoplastics. Currently methods of PHA extraction and purification from bacterial suspension use solvent or halogenated-based approaches which are costly and pose severe environmental damage. This invention describes a combined treatment of alkaline and homogenization for extracting and purifying PHA, with higher PHA purity and recovery.